Changes of Phytochemical, Antioxidant Characteristics of Sunflower Seed Roasting - Minh Phuoc Nguyen (Journal of Global Pharma Technology, 2020)
Sunflower seeds have various target specific biological activities. There has been an increase of awareness and interest in this valuable medicinal plant in recent times. Roasting is the key process in the production of value-added nuts having better taste, aroma, and a crunchy texture and exhibit enhanced crispiness. However changes of phytochemical, antioxidant characteristics of sunflower seeds during roasting have not been well understood. This research evaluated the roasing method affecting the phytochemical and antioxidant characteristics of sunflower seeds. The total polyphenol, flavonoid contents, the antioxidant activity characteristics in sunflower seeds were examined thoroughly. It may be desirable to use roasting at 200oC in 15 minutes to minimize the loss of total polyphenol, total flavonoid contents; maintain the most antioxidant activity. Keywords: Sunflower seed, Roasting, Total polyphenol, Total flavonoid, Antioxidant.